Subjective trial of the performance of the information trace method - Barendregt, L.G.; Benschop, C.A.; de Heer, T. (Information processing & management, 1985)
In a previous article [1] T. de Heer described an information retrieval system (FUZZIE) that uses the information trace method. Since then a statistical investigation has been made into the performance of FUZZIE. Subjects attributed a subjective ranking to answers produced by FUZZIE. On comparing the subjective ranking and the rankings attributed by FUZZIE, conclusions were made on the strengths and weaknesses of the information trace method.